Compressive damage and heat release of composite laminate with circular prefabricated defect, part II-numerical method. (1st April 2022) - Fu, Yutong; Wang, Shen; Yao, Xuefeng
Abstract: In this paper, the compressive damage and its corresponding heat dissipation of carbon fiber reinforced polymer (CFRP) composite laminates with prefabricated defects are investigated by means of the numerical method. First, the relationship between the temperature change and the damage of laminate is derived. Second, both the damage evolution and the corresponding energy dissipation of composite laminates with the prefabricated interlaminate defect are simulated. The numerical results are consistent with the experimental results. Finally, influences of the circular prefabricated defect's size are discussed by numerical models. These results play important roles in analyzing and evaluating damage of the composite laminates, which is significant for the damage detection and damage thermo-response analysis in engineering applications of composites.